Effect of the long-term storage methods on the stability of cartilage biomechanical parameters - Blanka Žaloudková; Šárka Sekorová; Barbora Kopecká; Daniel Kytýř (Acta Polytechnica CTU Proceedings)
Long-term stability of the tissue product in terms of mechanical parameters is a key factor for its expiration date. For the investigation of storage effects on the cartilage tissues the experimental mechanical loading test combined with XCT scanning for the irregular shape inspection was performed. The samples were preserved according to three different protocols using the deep-freezing and two types of saline solution preservation. The stability of the biomechanical parameters was tested within annual intervals. All samples were subjected to uni-axial compression loading using the in-house developed compact table top loading device in displacement-driven mode. Based on the measurements, the results are represented in the form of stress-strain curves and quantified as elastic modulus and ultimate compression stress. It can be concluded that no significant difference was found in neither the mechanical properties of the samples nor in the effects of each preservational method.